Manajemen Produktivitas Sumber Daya Manusia: Kajian Empiris Pengaruh Pelatihan, Kompensasi, Lingkungan Kerja, dan Motivasi terhadap Kinerja Produktif Karyawan - Juwendi Juwendi; Ghelan Okta Palahi; Indra Indra; Ezalita Desviyanti; Wahyudi Wahyudi (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Human Resource Management (HRM) occupies a central position in driving organizational productivity by optimizing how human capital is managed. This research investigates how four HRM dimensions training and development, compensation systems, workplace conditions, and work motivation collectively shape employee productivity outcomes. A quantitative survey design was adopted, targeting permanent employees at manufacturing firms in Banten Province. Using purposive sampling, 120 respondents were recruited and surveyed with a validated structured questionnaire. Data were subjected to multiple linear regression analysis. Findings reveal that each predictor exerts a statistically significant positive influence: training and development (t = 4.071; p = 0.000), compensation (t = 3.397; p = 0.001), work environment (t = 3.384; p = 0.001), and work motivation (t = 3.046; p = 0.003). Taken together, the four variables account for 67.4% of the variance in employee productivity (R² = 0.674; F = 59.821; p = 0.000). These results affirm that a holistic, integrated approach to HRM is indispensable for elevating workforce productivity and strengthening organizational competitiveness.